The Political Domination of Identity in Indonesian Political Controversy and Mitigation of Election 2024 - Fajri, Pujangga Candrawijayaning (Politeia: Jurnal Ilmu Politik, 2024)
The political practice of identity in a political reality is indeed a matter of discretion, given that identity itself is inherent to man. Practices of identity politics potentially have two significant impacts: positive and negative. This study seeks to look at the political impact of identity on some of Indonesia's political contestation experiences and provide constructive advice to mitigate something similar in the forthcoming 2024 elections. This research is qualitative and is accompanied by descriptive techniques of analysis by studying reference sources relevant to the research. The results of this study show that in the context of political controversy in Indonesia, identity politics has been shaped throughout the electoral momentum: Pilpres 2014, Pilkada DKI Jakarta 2019, and Pilpres 2019 were used as political strategies by hitting the identities of other candidates. The emergence of mainstream groups using religious symbols and provocative narratives as an attempt to catch the hearts of voters means that the course of electoral momentum tends to advance sentiment rather than argument. If identity politics continues to flourish, it will potentially give rise to fascism, separatism, and so on. To prevent the same from happening in the forthcoming 2024 elections, it would require mitigation efforts such as strengthening religious moderation, promoting political ethics and ideas of candidates, and increasing digital literacy for voters, so that the niche will createÂ quality electoral processes and outcomes.